Central Asia and its Asian neighbors : security and commerce at the crossroads - Lal, Rollie (Rand publications series ;, 2006)
The Asian states neighboring Central Asia have historic links and strong interests in the region. China, Iran, Afghanistan, India, and Pakistan are critical players in the security and economic issues that will determine the future of Central Asia and affect U.S. interests in the region. Although these Asian states do not agree on how to secure Afghanistan against threats, there is unanimous agreement that a stable Afghanistan is critical to their own security interests. By assessing the developing relations between Central Asia and its Asian neighbors, it is evident that each country stands to benefit from stability and economic growth in Central Asia, but opinion toward U.S. presence and policy in the region could be a point of conflict. The purpose of this monograph is to provide an assessment of the nature of Asian states' interest and influence in Central Asia in order to determine the development of these relationships and how they will shape strategic dynamics of Asia in the coming years.